The Anti-tumoral Effect of β-D-Mannuronic Acid (M2000) as a Novel NSAID on Treg Cells Frequency and MMP-2, MMP-9, CCL22 and TGFβ1 Gene Expression in Pre-surgical Breast Cancer Patients - Sarvenaz Kashefi; Hamid Ahmadi; Ramesh Omranipour; Habibollah Mahmoodzadeh; Fahimeh Jafarnezhad-Ansariha; Farzaneh Tofighi Zavareh; Abbas Mirshafiey (Iranian Journal of Allergy, Asthma and Immunology, 2019)
With respect to the role of chronic inflammation in the induction and progression of breast cancer (BC). The relationship between tumor and tumor microenvironment may be a hopeful strategy for BC therapy. According to the effect of β-D-Mannuronic acid (M2000) as a novel non-steroidal anti-inflammatory drug (NSAID) on BC murine model and 4T1 cell line, we started to study that was a phase II, randomized, controlled clinical trial. 24 women with BC were included in this study and were followed by fixed oral doses of M2000, 500 mg two times a day (6-8 weeks). Blood samples were collected at baseline and weeks 6-8. To compare the patterns of matrix metalloproteinase-2 (MMP-2), matrix metalloproteinase-9 (MMP-9), C-C motif chemokine ligand 22 (CCL22) and The transforming growth factor-beta 1 (TGFβ1) gene expression and T regulatory cells (Tregs) frequency of healthy women normal controls with BC patients, a set of 10 blood samples of  women healthy volunteers was collected. The gene expression was evaluated by quantitative Real-time PCR (qRT-PCR) and the frequency of Tregs was assessed by flow cytometry. Our results showed, reduction in MMP-2 (p=0.08), MMP-9 (p=0.03), CCL22 (p=0.003) and TGFβ1 (p=0.1) gene expression and Tregs frequency (p=0.01) which play a main role in the development of chronic inflammation, angiogenesis, tumorigenesis and metastasis. Our findings demonstrated that M2000 therapy as a novel designed NSAID had valuable therapeutic effects on BC. No adverse effects were observed following the use of M2000 after 6-8 weeks.